Response Particles (Balā, Naʿam, Ī) in the Holy Qur’an: A Semantic Study - هاشم, ستار جبار (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
If we ponder the letters of response in the Holy Quran, we find them scattered in many surahs. The ancients and moderns have dealt with them in the chapters of language and grammar and books of the meanings of grammar and readings. They are many in the language, as they counted them and found them (eleven letters) , which are: (Kala, Bala, Na’am, Ay, Idhan, La, In, Ajl, Bijl, Jalal, Jir) , and only five letters are mentioned in the Quran, which are: (Kala, Bala, Na’am, Ay, Idhan) , and because the research is limited to a number of pages, I have selected three letters from them: (Bala, Na’am, Ay) ; because of the relationship of similarity and difference in their linguistic and contextual meanings in which they appeared, and to reach knowledge of the variation in their meanings and methods of use in the Quranic contexts in which they appeared.